Grundtvigs gudstjenestesyn liturgisk - Rønkilde, Jette Bendixen (Grundtvig-Studier, 2015)
A Liturgical Theological Re-reading of Grundtvig’s View on Worship Through a description of well-known works by Grundtvig, the article examines how Grundtvig’s view on worship can be said to form an independent liturgical theological position, which the author characterizes as a theory of communication of worship. The examination takes the Anglo- American theory of worship, Liturgical Theology, as its starting point. Then, Grundtvig’s view on worship is reinterpreted against main currents and main issues of contemporary Liturgical Theology. The article demonstrates how structures in the works of Grundtvig and in liturgical theology parallel each other, an observation that frames Grundtvig as a proto liturgical theologian. Grundtvig’s specific liturgical theological position is firmly rooted in a trinitarian understanding of worship as a meeting place between God and human beings and the experience of worship as intrinsically bound to aesthetic experience. Grundtvig’s view of worship can therefore be deemed to be in keeping with an aesthetic Trinitarian view that significantly emphasizes the third article of faith in the patristic symbols and the practice of the assembly.